Using stable isotopes to identify major flow pathways in a permafrost influenced alpine meadow hillslope during summer rainfall period. Issue 5 (6th January 2020) - Xiao, Xiong; Zhang, Fan; Li, Xiaoyan; Zeng, Chen; Shi, Xiaonan; Wu, Huawu; Jagirani, Muhammad Dodo; Che, Tao
Abstract: Global warming has leaded to permafrost degradation, with potential impacts on the runoff generation processes of permafrost influenced alpine meadow hillslope. Stable isotopes have the potential to trace the complex runoff generation processes. In this study, precipitation, hillslope surface and subsurface runoff, stream water, and mobile soil water (MSW) at different hillslope positions and depths were collected during the summer rainfall period to analyse the major flow pathway based on stable isotopic signatures. The results indicated that (a) compared with precipitation, the δ 2 H values of MSW showed little temporal variation but strong heterogeneity with enriched isotopic ratios at lower hillslope positions and in deeper soil layers. (b) The δ 2 H values of middle‐slope surface runoff and shallow subsurface flow were similar to those of precipitation and MSW of the same soil layer, respectively. (c) Middle‐slope shallow subsurface flow was the major flow pathway of the permafrost influenced alpine meadow hillslope, which turned into surface runoff at the riparian zone before contributing to the streamflow. (d) The slight variation of δ 2 H values in stream water was shown to be related to mixing processes of new water (precipitation, 2%) and old water (middle‐slope shallow subsurface flow, 98%) in the highly transmissive shallow thawed soil layers. It was inferred that supra‐permafrost water levels would be lowered to a less conductive, deeper soil layer under further warming and thawing permafrost, which would result in a declined streamflow and delayed runoff peak. This study explained the "rapid mobilization of old water" paradox in permafrost influenced alpine meadow hillslope and improved our understanding of permafrost hillslope hydrology in alpine regions. Abstract : The key findings Mixing of new water of precipitation (2%) with a large portion of old water (98%) in thawed soil layers dampened the isotopic variation of stream water. Shallow subsurface flow was the major flow pathway in permafrost influenced alpine meadow hillslope, which turned into surface runoff at the riparian zone before supplying streamflow. Frozen soil is important to promote the hillslope runoff generation by maintaining supra‐permafrost water level to the highly transmissive shallow soil layer.